Synthesis of Logic Circuits Using Fractional-Order Dynamic Fitness Functions - Reis, Cecília (2019)
This paper analyses the performance of a genetic algorithm using a new concept, namely a fractional-order dynamic fitness function, for the synthesis of combinational logic circuits. The experiments reveal superior results in terms of speed and convergence to archieve a solution.